Streptococcus pneumoniae serotype 1 capsular polysaccharide induces CD8CD28 regulatory T lymphocytes by TCR crosslinking. - Janina Mertens; Mario Fabri; Alessandra Zingarelli; Torsten Kubacki; Sonja Meemboor; Laura Groneck; Jens Seeger; Martina Bessler; Helena Hafke; Margarete Odenthal; Joan G Bieler; Christoph Kalka; et al. (PLoS Pathogens, 2009)
Zwitterionic capsular polysaccharides (ZPS) of commensal bacteria are characterized by having both positive and negative charged substituents on each repeating unit of a highly repetitive structure that has an alpha-helix configuration. In this paper we look at the immune response of CD8(+) T cells to ZPSs. Intraperitoneal application of the ZPS Sp1 from Streptococcus pneumoniae serotype 1 induces CD8(+)CD28(-) T cells in the spleen and peritoneal cavity of WT mice. However, chemically modified Sp1 (mSp1) without the positive charge and resembling common negatively charged polysaccharides fails to induce CD8(+)CD28(-) T lymphocytes. The Sp1-induced CD8(+)CD28(-) T lymphocytes are CD122(low)CTLA-4(+)CD39(+). They synthesize IL-10 and TGF-beta. The Sp1-induced CD8(+)CD28(-) T cells exhibit immunosuppressive properties on CD4(+) T cells in vivo and in vitro. Experimental approaches to elucidate the mechanism of CD8(+) T cell activation by Sp1 demonstrate in a dimeric MHC class I-Ig model that Sp1 induces CD8(+) T cell activation by enhancing crosslinking of TCR. The expansion of CD8(+)CD28(-) T cells is independent, of direct antigen-presenting cell/T cell contact and, to the specificity of the T cell receptor (TCR). In CD8(+)CD28(-) T cells, Sp1 enhances Zap-70 phosphorylation and increasingly involves NF-kappaB which ultimately results in protection versus apoptosis and cell death and promotes survival and accumulation of the CD8(+)CD28(-) population. This is the first description of a naturally occurring bacterial antigen that is able to induce suppressive CD8(+)CD28(-) T lymphocytes in vivo and in vitro. The underlying mechanism of CD8(+) T cell activation appears to rely on enhanced TCR crosslinking. The data provides evidence that ZPS of commensal bacteria play an important role in peripheral tolerance mechanisms and the maintenance of the homeostasis of the immune system.